Accelerating Creativity as a Pinnacle of Professional Practice in Accountancy, Early Childhood Education and Psychology in Nigeria - Ugboaku, Chinyere J; Ugboaku, Patrick U; Obede-Ohen, Dumkelechuku C.; Bekaren, Alex U; Ezekwueme, Anthony C; Nwafor, Elizabeth E (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
The study investigated the role of creativity in professional practice among three distinct fields in Nigeria- Accountancy, Early Childhood Education and Psychology- aiming to assess the levels of creative application, perception and challenges across the professions. a descriptive survey design was employed, involving 150 participants (50 from each profession) aged 30 to 60 years. Data were collected using a researcher- developed instrument, the creativity in professional practice questionnaire (CPPQ), comprising 16 likert-scale items. The reliability of the instrument was confirmed with a Cronbach’s alpha of de .76. Descriptive statistics and inferential analyses, including one-way ANOVA and independent t-tests, were used to test four null hypotheses at a 0.05 significance level. Results indicated that Early Childhood Educators reported the highest average creativity score (M-4.29), followed by Psychologists (M=3.91) and Accountants (M=3.40). ANOVA revealed a statistically significant difference in creativity application across professions (f(2,147)=9.86,p<0.001). Also, no significant difference was observed on years of experience (t-1.32,p<0.0188). Professional-specific barriers were also statistically significant (f(2,147)=6.45,p<.0.002), similarly, significant differences were found across age groups (f(2,147)=5.27, p<0.006) groups with younger professionals (ages 30-40) showing greater creative engagement. However, Accountants’ citing regulatory restrictions, psychologists citing institutional rigidity and educators noting lack of instructional materials. The study concludes that creativity is a vital but unevenly distributed professional skill in Nigeria. It recommends that professional bodies and policymakers incorporate creativity-enhancing strategies into training, workplace practice and national development plans to foster innovation across sectors.